The Entrepreneurship as a Strategy for Employment Generation in Crisis Situations - Aguilar Méndez, Denisse Loreth; Robles Santana, Yadira Rosanna; Mera Bravo, Eliana Pilar (Journal of Ecohumanism, 2024)
This research delves into the importance of entrepreneurship in crisis situations, focusing on a detailed analysis of two of the most significant events in terms of economic and social repercussions that have taken place in Ecuador, such as: The earthquake of April 16, 2016 that affected the provinces of Manabí and Esmeraldas and the COVID 19 pandemic, a global crisis that also affected the country. The methodology used to develop this research combined qualitative and quantitative approaches, using a transversal-correlational design and considering two temporal events for data collection. Direct observation was used as research techniques, which made it possible to monitor the ventures that emerged in response to both events. These data were complemented with a survey applied to 353 inhabitants of Pedernales. The results show that entrepreneurship served as a mechanism to process economic crises by reallocating resources and generating sources of income, allowing them to develop creativity and innovation within businesses. In both crises, different patterns were evident; however, in both crises the implementation of formal and informal enterprises predominated. To guarantee the sustainability of these ventures that were generated in the context of crisis, it is concluded that the implementation of strategies is required to remain competitive in the market.